'Cease and desist?' The persistence of Marlboro brand imagery in racing video games. Issue Volume 29:Issue e1(2020) (5th February 2020) - Forsyth, Susan; McDaniel, Patricia A
Abstract : Background: Since 1972, Philip Morris (PM) has sponsored motorsports. Racing video games are a popular genre among youth and often emulate the branding of their real-life counterparts, potentially exposing youth to tobacco imagery. We examined racing video games for the presence of Marlboro imagery and explored the history of efforts to remove or regulate such imagery. Methods: We searched the Truth Tobacco Industry documents for relevant documents and used information from video game-related websites and game play videos to identify racing video games that contained Marlboro trademarks and imagery. We also collected information on the Entertainment Software Ratings Board's (ESRB) tobacco-specific and overall game ratings. Findings: In 1989, negative publicity surrounding the presence of Marlboro logos in racing games led PM to threaten legal action against two game makers for copyright infringement. PM also launched a media campaign promoting this intervention as evidence of its commitment to youth smoking prevention. Nonetheless, we identified 219 video games from 1979 to 2018 that contained Marlboro trademarks and/or Marlboro-sponsored drivers and livery. Among the games in our sample with an ESRB game rating, all but one received an 'E, ' indicating appropriateness for everyone, and all but three lacked tobacco content descriptors. Conclusion: Racing video games have been and continue to be a vehicle for exposing adolescents to the Marlboro brand. Because voluntary efforts by PM and the video game industry to prevent youth exposure to tobacco brands in video games have been ineffective, USA and international policy-makers should prohibit tobacco content in video games.